Managing Knowledge in Organizations: A Nonaka’s SECI Model Operationalization - Farnese, Maria Luisa; Barbieri, Barbara; Chirumbolo, Antonio; Patriotta, Gerardo (Frontiers in Psychology, 2019)
Purpose. The SECI model (Nonaka, 1994) is the most well-known conceptual framework for knowledge generation in organizations, a crucial drive for competitive advantage. To date, however, empirical support for this theorization has been overlooked. The present study aimed to provide an evidence-based groundwork for the SECI model by testing a multidimensional questionnaire (KMSP-Q), designed to capture the knowledge conversion modes theorized by Nonaka. Methodology. In a twofold study, the knowledge generation construct was operationalized with generating the KMSP-Q. Specifically, Study One tested its 8-dimensional structure through exploratory and confirmatory factorial analyses on 372 employees from different sectors. Study Two examined the construct validity and reliability by replicating the KMSP-Q factor structure in knowledge intensive contexts (on a sample of 466 health-workers), and by investigating the unique impact of each dimension on some organizational outcomes (i.e. performance, innovativeness, collective efficacy). Findings. The overall findings highlighted that the KMSP-Q is a psychometrically robust questionnaire in terms of both dimensionality and construct validity, the different knowledge generation dimensions being specifically linked to different organizational outcomes. Research/Practical implications. The KMSP-Q may contribute to actualize and provide empirical consistency to the theory underlying the SECI model. Moreover, it allows for the monitoring of the organization’s capability to manage new knowledge and detecting the strengths/weaknesses of KM policies and related programs. Originality/value. This paper proposes a comprehensive measure of knowledge generation in work contexts, highlighting processes that organizations are likely to promote in order to improve their performance through the management of their knowledge resources.